Mobile Learning to Improve Student Collaborative Skills: An Alternative to Online Learning in the Era of Covid-19 Pandemic - Dwikoranto, D.; Setiani, Rahyu; Prahani, Binar Kurnia; Mubarok, Husni (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2020)
This research aimed to produce a valid and effective mobile learning model and tools as an alternative to online learning solutions in the era of the Covid-19 pandemic. The tutorial tools are: tutorial activity design, tutorial activity unit, student activity sheet, and collaborative ability test. The trial design used a Pre-Experiment with a one group pre-test and post-test design. The research subject was the Pre-service Primary Teachers (PPTs) programming the elementary concept science course for the registration period of 2020. The data collection instruments included: (1) tutorial tool validity assessment sheet and (2) collaborative ability test. The research data were in the form of pre-test scores and post-test scores after going through a series of prerequisite tests: normality test and homogeneity test which were then analyzed using paired t-test. The mean level of improvement in the pre-test and post-test scores were calculated using the gain score. The results showed that: (1) the development of mobile learning which was included in the content and construct in the valid category, and supported by tutorial tools was included in the valid category and (2) the developed mobile learning was included in the effective category because of the significant increase in student collaborative abilities in limited trials and extensive trials in moderate criteria and students respond positively to the tools and tutorial processes. Based on the results above, it can be concluded that the development of mobile learning was valid and effective to improve student collaborative abilities.